THE NUMERICAL-FIELD ANALYSIS OF THE MAGNETIC FIELD AND THE ELECTRICAL QUANTITIES IN THE TURBOGENERATOR STATOR UNDER AUTONOMOUS UNBALANCED LOADING - V. I. Milykh (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. Assessing the impact of load asymmetry of turbogenerator (TG) on the magnetic field distribution, on the electrical and energy processes in it based on the numerical-field analysis within the constraints regulated by the standards. Methodology. The calculation model of TG has been constructed on the method of symmetrical components of the three-phase current system. The formed asymmetric system of the currents is used for multi-position numerical calculations of rotating magnetic fields. The temporal functions of the electromagnetic quantities which are subjected to the harmonic analysis are obtained on this basis. Results. Test calculations are conducted on a three-phase 35 MW TG during his work under autonomous unbalanced loading. The analysis of the temporal functions of the magnetic induction at different points of the TG stator and also similar functions of the magnetic flux linkage, EMF phase stator windings and other variables have been executed. Originality. Problems of exploitation of turbo-generators under unbalanced loading are detected by the consideration of their electromagnetic system on the whole, but not their simplified local parts, as usual. It has been shown that the temporal functions of EMF of the phase stator windings under unbalanced loading significantly differ in shape from sine waves and from each other and contain a number of significant upper harmonics. It has been detected that the phase currents would contain not only the first but also significant upper harmonics under unbalanced loading. Practical value. Analysis of the work of TG under unbalanced loading showed the «top» level of problems of electromagnetic character. It has been established that the function of the magnetic induction at the fixed points of the magnetic system on the whole have been changed but not in principle. The temporal functions of EMF, and, hence, the voltage of the stator phase windings significantly differ in shape from sine waves and from each other, there is a considerable imbalance of active powers generated by the individual phase windings of the stator. The information provided will allow the measures to ensure a durable and reliable operation of turbo-generators.